Clinical response to therapeutic plasmapheresis and intravenous immunoglobulin in pregnancies complicated by alloimmunization despite persistently high titers: Report of two cases - Nedaa Bahkali; Ebtihal Alhawsawi; Kholoud Althakafi; Kholoud Arab; Almotasimbellah Rayes; Maha A. Badawi (Clinical Case Reports, 2023)
Key Clinical Message Plasmapheresis and IVIG use in cases of alloimmunization during pregnancy are effective strategies when severe early fetal anemia is anticipated. Despite no change in antibody titer levels before and after plasmapheresis, clinical response was observed in both fetuses, and both had an excellent obstetrical outcome. Abstract Hemolytic disease of the fetus and newborn is a potentially lethal complication of alloimmunization, and intrauterine fetal blood transfusion (IUBT) is the standard treatment and care plan for severe fetal anemia. However, IUBT is technically unattainable before 20 weeks of gestation. Plasmapheresis and intravenous immunoglobulin (IVIG) are the two treatment modalities described in the literature that postpone the need for transfusion until after 20 weeks. Here, we present two cases of alloimmunization (one with anti‐Kell and the other with anti‐D). Both had poor outcomes in previous pregnancies because of the early development of severe fetal anemia and hydrops before 24 weeks of gestation. Both patients underwent three sessions of plasmapheresis before 18 weeks, followed by weekly IVIG infusion, which continued until 23–27 weeks of pregnancy. Antibody titers were measured before and after plasmapheresis. In addition, weekly MCA Doppler was performed to monitor the development of severe fetal anemia requiring blood transfusion, which was diagnosed when the peak systolic velocity (PSV) was 1.5 multiples of the median or more. The first patient underwent IUBT at 24 weeks and the second at 28 weeks, as indicated by the MCA Doppler. Both patients were delivered by cesarean section, the first at 34 weeks and the second at 36 weeks, for different obstetrical indications. Both pregnancies resulted in a live birth. We conclude that the use of plasmapheresis and IVIG in alloimmunization during pregnancy is an effective treatment strategy when severe early fetal anemia is anticipated before 20 weeks of gestation. Despite no change in antibody titer levels before and after plasmapheresis, a clinical response was observed in both fetuses, and both had excellent obstetrical outcomes.